The effect of two ectomycorrhizal fungi, Paxillus involutus and Suillus tomentosus, and of Bacillus subtilis on Fusarium damping-off in jack pine seedlings - Hwang, S.F.; Chakravarty, P.; Chang, K.-F. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1995)
Two species of ectomycorrhizal fungi, Paxillus involutus and Suillus tomentosus, and a bacterial strain of Bacillus subtilis, were tested against Fusarium moniliforme, the causal agent of damping-off in jack pine (Pinus banksiana) seedlings. Both P. involutus and B. subtilis inhibited in vitro growth of F moniliforme. The culture filtrates of P. involutus and B. subtilis were toxic to F moniliforme, but chlamydospore formation of F moniliforme was observed. Greater jack pine seedling survival was observed when co-inoculated with P. involutus and B. subtilis than with F moniliforme alone. S. tomentosus neither inhibited in vitro growth of F moniliforme nor increased survival of jack pine seedlings against F moniliforme. F moniliforme reduced ectomycorrhiza formation on jack pine seedlings by P. involutus and S. tomentosus. The number of colony forming units of F moniliforme was significantly reduced when seedlings were inoculated with P. involutus and B. subtilis alone or in combination. S. tomentosus, on the other hand, did not reduce the number of colony forming units of F moniliforme. The suppression of F moniliforme growth by P. involutus and B. subtilis involved production of antifungal compounds.